Calculating Wins over Replacement Player (WORP) for NHL goaltenders - Shea, S. M.; Baker, C. E. (Journal of Quantitative Analysis in Sports, 2012)
We present formulas for calculating wins over replacement player (WORP) for NHL goaltenders. If a team's primary objective is victory over its opponent, then a player's value may best be determined by his ability to help his team win games. Furthermore, a player's contribution to his team's wins would be a universal unit of measure and would allow for direct comparisons of goalie and skater production. We found inspiration for our work in Keith Woolner`s calculations of "value over replacement player" (VORP) for MLB players, and we will make use of Bill James` "Pythagorean Method" as it was applied to the NHL by Cochran and Blackstock in 2009.